1993
DOI: 10.1016/1010-7940(93)90141-w
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal nerve block, interpleural analgesia, thoracic epidural block or systemic opioid application for pain relief after thoracotomy?

Abstract: The purpose of this study was to investigate the effect of different pain-relief methods (regional and systemic) following thoracotomies on the cardiovascular system, pulmonary gas exchange, various endocrine parameters and subjective perception. A further aspect was to evaluate the benefits of interpleural analgesia as a new regional technique against already established regional techniques, such as intercostal nerve block and thoracic epidural block. All postoperative pain methods led to a significant time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…7,8,10,11 Bachmann-Mennenga et al, 10 Von Dossow et al 11 and Davies et al 7 showed that VAS at rest in the presence of thoracic epidural ranged between 1 and 6 cm which is comparable with the range of VAS R in the current study. Furthermore, in a recent meta-analysis, Davies et al 7 showed that the incidence of hypotension was 19% during TEA which is comparable with the 24% incidence of hypotension reported in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…7,8,10,11 Bachmann-Mennenga et al, 10 Von Dossow et al 11 and Davies et al 7 showed that VAS at rest in the presence of thoracic epidural ranged between 1 and 6 cm which is comparable with the range of VAS R in the current study. Furthermore, in a recent meta-analysis, Davies et al 7 showed that the incidence of hypotension was 19% during TEA which is comparable with the 24% incidence of hypotension reported in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…[ 4 ] The lack of benefit has been shown in multiple studies and this technique is not recommended for post-thoracotomy pain. [ 4 60 61 62 ]…”
Section: Interventional Techniquesmentioning
confidence: 99%
“…While there are reports which address safety and advantages of intrapleural block in postthoracotomy patients [4350], most other studies showed little or no benefit for ISP [11, 5155]. As an interesting finding, intrapleural block could not decrease epidural analgesia requirement and have little effect on intercostal incisional pain after thoracotomy, too [11, 57].…”
Section: Treatmentsmentioning
confidence: 99%